2015
DOI: 10.1016/j.celrep.2015.03.036
|View full text |Cite
|
Sign up to set email alerts
|

ATRX Plays a Key Role in Maintaining Silencing at Interstitial Heterochromatic Loci and Imprinted Genes

Abstract: SummaryHistone H3.3 is a replication-independent histone variant, which replaces histones that are turned over throughout the entire cell cycle. H3.3 deposition at euchromatin is dependent on HIRA, whereas ATRX/Daxx deposits H3.3 at pericentric heterochromatin and telomeres. The role of H3.3 at heterochromatic regions is unknown, but mutations in the ATRX/Daxx/H3.3 pathway are linked to aberrant telomere lengthening in certain cancers. In this study, we show that ATRX-dependent deposition of H3.3 is not limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
170
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(178 citation statements)
references
References 48 publications
5
170
1
2
Order By: Relevance
“…The inactivation of EHMT2 also affects the maintenance of the DNA methylation imprint at the Slc38a4 gDMR, but not at gDMRs of other imprinted loci, which highlights the existence of locus-specific mechanisms of maintenance of imprinted DNA methylation. Slc38a4 differs from other imprinted gDMRs in that it shows no ZFP57 binding (Saadeh and Schulz 2014;Strogantsev et al 2015), displays no allelic ATRX binding and H3.3 incorporation (Voon et al 2015), and also lacks H3K9me3 in ES cells. These marked differences could explain why this gDMR uniquely relies on alternative, EHMT2-dependent mechanisms for the maintenance of its germline-derived allelic DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…The inactivation of EHMT2 also affects the maintenance of the DNA methylation imprint at the Slc38a4 gDMR, but not at gDMRs of other imprinted loci, which highlights the existence of locus-specific mechanisms of maintenance of imprinted DNA methylation. Slc38a4 differs from other imprinted gDMRs in that it shows no ZFP57 binding (Saadeh and Schulz 2014;Strogantsev et al 2015), displays no allelic ATRX binding and H3.3 incorporation (Voon et al 2015), and also lacks H3K9me3 in ES cells. These marked differences could explain why this gDMR uniquely relies on alternative, EHMT2-dependent mechanisms for the maintenance of its germline-derived allelic DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a genome-wide study revealed that ATRX-dependent H3.3 deposition is not limited to telomeres and pericentromeric regions, but also occurs at imprinted loci. The interplay of ATRX and H3.3 at imprinted alleles is essential for the maintenance of H3K9me3 modification, gene repression and proper allelic expression (Voon et al, 2015). In another study, H3.3 was found to be required for the repression of key developmental genes via the recruitment of PRC2 by HIRA; furthermore, suppression of endogenous retrovirus element was dependent on DAXX, H3.3 and KAP1 Elsasser et al, 2015).…”
Section: The Regulation Of Chromatin Dynamics By Variant H33mentioning
confidence: 95%
“…As a consequence, new nucleosomes can form, ultimately ensuring genome stability. Moreover, in recent studies in mouse ES cells using chromatin immunoprecipitation combined with high-resolution genome-wide sequencing (ChIP-seq), it was revealed that H3.3 is also enriched at a subset of inactive genes, telomeres and repetitive elements such as endogenous retroviral elements (ERVs) (Elsasser et al, 2015;Goldberg et al, 2010), where ATRX/DAXX is required for H3.3 deposition and the maintenance of a repressive chromatin state (Elsasser et al, 2015;Goldberg et al, 2010;Lewis et al, 2010;Voon et al, 2015). Meanwhile, H3.3 is also distributed in other regions such as cis-regulatory elements Goldberg et al, 2010;Mito et al, 2007), and plays an important part in the regulation of gene expression .…”
Section: The Properties Of H33 Compared With Its Canonical Counterpartsmentioning
confidence: 99%
“…3,4 Transkripsiyonel düzenleyici ATRX genindeki fonksiyon kaybı mutasyonları ve telomeraz enzimini kodlayan TERT geninin promotör bölgesindeki regülasyon, kromatinin yeniden modellenmesine katılan genlerdeki mutasyonlar nöroblastom gelişimi ve ilerlemesiyle ilişkilidir. 7,8 Kodlamayan bölgelerdeki somatik mutasyonlar da nöroblastom progresyonuyla ilişkilen-dirilmiştir. Özellikle, tümör baskılayıcı ve aday tümör baskılayıcı genlerin kodlamayan bölgelerin-deki mutasyonlar, yüksek risk nöroblastomda oldukça etkilidir.…”
Section: Gen Kisaltmalariunclassified
“…ATRX, metilasyon ile sessizleştirilen transpozon elementler, imprintlenmiş genler ve telomerleri içeren bölgelerde H3.3 (Histon 3 varyantı) birikiminden sorumludur. 7 Telomer, kromozomların uç bölgelerinde bulunan ve kromozomların stabilitesini sağlayan tekrar dizileridir. Ökaryotlarda, her replikasyonda telomerler kısalmaktadır ve böylece hücrenin proliferasyon yeteneği kısıtlanmaktadır.…”
unclassified